2014
DOI: 10.1007/s00520-014-2426-6
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough cancer pain: a comparison of surveys with European and Canadian patients

Abstract: Breakthrough cancer pain in both Canadian and European patients greatly impacts their daily living, and both groups of patients had similar experiences with breakthrough cancer pain. Currently, this pain is not adequately managed for many patients. The role for new analgesic treatments in management of breakthrough cancer pain needs further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
1
21
1
Order By: Relevance
“…We found that the prevalence of BTP varied between countries, from 14% to 75%, in contrast to other studies 8 29. There may be different reasons for this, in particular, that the other studies were specifically designed to characterise BTP, while ours was not.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…We found that the prevalence of BTP varied between countries, from 14% to 75%, in contrast to other studies 8 29. There may be different reasons for this, in particular, that the other studies were specifically designed to characterise BTP, while ours was not.…”
Section: Discussioncontrasting
confidence: 90%
“…The Bedard et al 29 study also used a specifically developed registration tool for presence and management of BTP, and found no differences in the incidence of BTP when comparing data from 94 Canadian and 1000 European PC patients. On the other hand, an international survey published in 2004 demonstrated that physicians from English-speaking countries were significantly more likely to report BTP than were physicians from other countries 7.…”
Section: Discussionmentioning
confidence: 99%
“…In an Italian survey, 21 of 118 physicians at dedicated palliative care institutions select fentanyl alone or fentanyl with other opioids as their drug of choice for controlling BTcP (15). On the other hand, the percentage of Canadian patients with BTcP who had been prescribed fentanyl was only 2.9% (16). Based on comparison with the physician surveys of other countries, transmucosal fentanyl is used more frequently in Korea than in Canada, but less frequently than in European countries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a mismatch between temporal characteristics of BTcP and the mechanisms of rescue medications may result in suboptimal pain management and undesirable adverse effects for patients, such as sedation, confusion, and fatigue (14). Recent research in other countries has shown that many physicians still use conventional rescue medications despite the availability of more appropriate opioids (15,16). However, there is little data regarding the management of BTcP among Korean physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of BTP has been reported to range from 40% to 80% and is associated with patients' morbidity . In consideration of its impacts on cancer patients, adequate management of BTP is required but is still suboptimal …”
Section: Introductionmentioning
confidence: 99%